Collectibility Improvement in PT. Kaltim Prima Coal Receivables Management: A Framework Roadmap Proposal - Zuhri Ruslan; Anggoro Budi Nugroho (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Importance of efficient working capital management is indisputable given that a firm’s viability relies on the financial manager’s ability to effectively manage receivables, inventory, and payables. One of widely used measurement to calculate the effectiveness of working capital management is Cash Conversion Cycle. Cash Conversion Cycle will calculate how much capital tied up in inventory and receivable by measure how many days it takes for coal from exposed until it sold to the buyer, add with how many days it takes to collect the payment from the buyer, and minus with how many days it took for the invoices to be paid. A good working capital will allow Company to pay all its liabilities when due using payment received from the customers. Traditional Cash Conversion Cycle is calculated using items from Financial Statement. However, it is proofed to be overstated compare to actual calculation. Based on comparison with Cash Conversion Cycle of another company listed in Indonesian Stock Exchange, Cash Conversion Cycle of PT Kaltim Prima Coal seems to be superior with lower days it needs to convert inventory into cash and longer time to pay its payables. The research found that based on the regression method, days of late payment and sales amounts of late payment have significant relationship with Profit. Days of late payment and sales amounts of late payment has significant relationship with ROA. And, Days of late payment and sales amounts of late payment also has significant relationship with NPM. The research also found that Average Age of Inventory has negative relationship with Profit, ROA, ROE, and has positive relationship with NPM. Average Collection Period has negative relationship with Profit and ROEand has positive relationship with NPM and ROA. Average Payment Period has positive relationship with Profit, and has negative relationship with NPM, ROA and ROE. Day delay has negative relationship with Profit, ROE and NPM, and has positive relationship with COGS and ROA. Amount delay has positive relationship with Profit, COGS, ROA, ROE and NPM.